Synthesis and antimicrobial evaluation of 5-aryl-1, 2, 4-triazole-3-thione derivatives containing a rhodanine moiety. Issue 15 (1st August 2015) - Li, Chao; Liu, Jia-Chun; Li, Ya-Ru; Gou, Cheng; Zhang, Mei-Ling; Liu, Hong-Yan; Li, Xiao-Zhen; Zheng, Chang-Ji; Piao, Hu-Ri
Graphical abstract